Designing Vocabulary Learning Media for Junior School Students: A Theoretical Approach: English - Arif Bulan; Karmila; Muhammad Yanbaqi Abidin Putra (CV. Multi Kreasi Media, 2022)
−Vocabulary is one of the most important components of English. This study aims to describe the steps of designing or developing vocabulary learning media theoretically. This study uses the library study method. This method emphasizes textbooks, journals, and other relevant sources as sources of data and theoretical studies. The textbooks used in this study are the leading textbooks that become references in the study of vocabulary. The journals used in this study are also relevant and current journals that reveal vocabulary discussions. The study results indicate that instructional media design must include the stages of analysis, design, development, implementation, and evaluation.